2017
DOI: 10.7181/acfs.2017.18.2.89
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Analysis of Superior Orbital Fissure Width in Korean Adults using Computed Tomography Scans

Abstract: BackgroundThe superior orbital fissure is a small area that connects the middle cranial fossa and the orbit. Many studies have measured the size of the superior orbital fissure. However, there is no standard value for the size of the superior orbital fissure. Therefore, we conducted this study to provide the average size of the superior orbital fissure in Korean adults.MethodsWe measured the widths of the superior orbital fissures of 142 patients using computed tomography scans. Because the width of the superi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…The widths of the superior orbital fissures were 3.78±0.92 mm on the right (maximum, 6.53; minimum, 2.04), 3.79±0.96 mm on the left side (maximum, 6.98; minimum, 2.04) and 3.79±0.93 across both sides in male and 3.69±1.18 mm on the right (maximum, 6.67; minimum, 1.95), 3.62±1.34 mm on the left (maximum, 7.47; minimum, 1.35) and 3.65±1.26 mm across both sides in female patients. They suggested that a narrow superior orbital fissure may be a risk factor for the superior orbital fissure syndrome [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The widths of the superior orbital fissures were 3.78±0.92 mm on the right (maximum, 6.53; minimum, 2.04), 3.79±0.96 mm on the left side (maximum, 6.98; minimum, 2.04) and 3.79±0.93 across both sides in male and 3.69±1.18 mm on the right (maximum, 6.67; minimum, 1.95), 3.62±1.34 mm on the left (maximum, 7.47; minimum, 1.35) and 3.65±1.26 mm across both sides in female patients. They suggested that a narrow superior orbital fissure may be a risk factor for the superior orbital fissure syndrome [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…They measured the distance of SOF from the substantia nigra as 38.4 ± 7.6 mm in men and 36.5 ± 6.1 mm in women. Park et al [18] also analyzed CT images of 142 patients and measured the width of the SOF. They found the width of the SOF 3.79 ± 0.93 mm in men and 3.65 ± 1.26 mm in women.…”
Section: Radiological Anatomy Of the Superior Orbital Fissurementioning
confidence: 99%